First results of the searching of asteroids based on the data of FON-Dushanbe processed plates - Yizhakevych, O. M.; Mullo-Abdolov, A. Sh.; Relke, H. V.; Kokhirova, G. I.; Pakuliak, L. K.; Andruk, V. M. (Одеські астрономічні публікації, 2018)
We have initiated the search of asteroids and comets on the basis of the processing digital images of plates obtained in the framework of FON project (the photographic survey of the northern hemisphere), Dushanbe section of the observational program. The result is the catalog of positions of the Solar System minor bodies. Observations were obtained in 1985-1992 at the Gissar Astronomical observatory of TajAPHI (Institute of Astrophysics of the Academy of Sciences of Tajikistan) on the Zeiss-400 astrograph (Marsden’s code 190, D/F=400/2000 mm). The plate collection includes around 1570 negatives covered the northern hemisphere from – 8° to + 90°. The plate digitization has started in 2017 after the commercial scanner Microtek ScanMaker 1000XL Plus was provided. The scanner was previously tested for systematic errors and proved for suitability for digitizing photographic plates. The joint research of MAO NAS of Ukraine and Gissar observatory on Dushanbe glass collection reduction has started in 2017. The astrometric reduction of digitized plates is conducted using the software developed in MAO NAS of Ukraine running in the LINUX/MIDAS/ROMAPHOT complex. To the current moment, 10% of the collection (171 plates) has been processed. For each fixed object we obtain positions in the TYCHO2 reference system. For stars in the magnitude range 5m-17m positional errors were estimated as ±0.36 arcsec, and B-magnitudes’ errors were found ± 0.12m . Stars and galaxies are not the only objects registered on the plates. During the observations, such objects as comets and asteroid could occasionally get on the picture. Here, we present the first results of the search for such objects on the FON photographic plates. The search and the evaluation of the convergence of minor bodies’ observed positions with the theoretic predictions are carried out online by jpl ephemerid service ( https://ssd.jpl.nasa.gov/sbfind).